2023
DOI: 10.3389/fimmu.2023.1119315
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and causal analysis for inflammatory genes and the risk of Parkinson’s disease

Abstract: BackgroundThe dysfunction of immune system and inflammation contribute to the Parkinson’s disease (PD) pathogenesis. Cytokines, oxidative stress, neurotoxin and metabolism associated enzymes participate in neuroinflammation in PD and the genes involved in them have been reported to be associated with the risk of PD. In our study, we performed a quantitative and causal analysis of the relationship between inflammatory genes and PD risk.MethodsStandard process was performed for quantitative analysis. Allele mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 191 publications
(77 reference statements)
0
5
0
Order By: Relevance
“…For instance, HLA-DRB1 ( Le Guen et al, 2023 ) has been identified as an immune-related PD gene. Additionally, polymorphisms in STX1B ( Wang et al, 2015 ) and CCDC62 ( Lauterbach, 2012 ; Yi et al, 2023 ) are connected to PD. Numerous other DNA methylations, such as CRHR1 ( Cheng et al, 2020 ; Rasmi et al, 2023 ) and ABCB9 ( Chuang et al, 2017 ) have implications on PD development.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, HLA-DRB1 ( Le Guen et al, 2023 ) has been identified as an immune-related PD gene. Additionally, polymorphisms in STX1B ( Wang et al, 2015 ) and CCDC62 ( Lauterbach, 2012 ; Yi et al, 2023 ) are connected to PD. Numerous other DNA methylations, such as CRHR1 ( Cheng et al, 2020 ; Rasmi et al, 2023 ) and ABCB9 ( Chuang et al, 2017 ) have implications on PD development.…”
Section: Discussionmentioning
confidence: 99%
“…Parkinson’s disease (PD) is a common and complex neurological disorder that exhibits classical motor dysfunctions, including bradykinesia, resting tremor and gait disturbance, and non-motor features, such as psychiatric symptoms, sleep disorder and cognitive impairment ( 36 ). Epidemiological studies have revealed that both genetic and environmental factors are attributable to PD ( 36 41 ).…”
Section: Parkinson’s Diseasementioning
confidence: 99%
“…Hence any of them alone could not be an appropriate diagnostic or prognostic biomarker for PD. It is worth examining, however, whether these SNPs could be integrated effectively into polygenic risk score analysis ( 73 ) in combination with SNPs of IL-6, TNF-α and many other PD-related genes ( 41 ).…”
Section: Parkinson’s Diseasementioning
confidence: 99%
“…Many genes contribute to the pathogenesis of PD, including α-synuclein ( SNCN ), leucine-rich repeat kinase 2 ( LRRK2 ), glucocerebrosidase ( GBA ), vacuolar protein sorting associated protein 35 ( VPS35 ), phosphatase homolog-induced kinase ( PINK1 ) and Parkinson protein 7 ( PAPK7 ) [ 3 , 4 ]. The interaction between the susceptible genes and environmental elements influences the onset of PD [ 5 ].…”
Section: Introductionmentioning
confidence: 99%